The role of tailings concentration on flocculation behavior in a two-stage feedwell: Insights from CFD-PBM coupling modelling - Xiaoyu Wang; Baoyu Cui; Xuetao Wang; Jizong Wu; Yunhai Zhang; Congjun Li (Journal of Environmental Chemical Engineering, 2026)

Lithology Identification Method for Marine–Continental Transitional Shale Systems Based on Superposition Reconstruction: A Case Study of the Shanxi Formation, Ordos Basin, China - Xinglei Song; Congjun Feng; Zhen Qiu; Sizhong Peng; Teng Li; Pengfei Wu; Zhiqiang Chen; Mengsi Sun (Natural Resources Research, 2026)

Correction: Nutritional status and drug resistance in EGFR-mutant NSCLC: a retrospective cohort study on almonertinib efficacy - Chao Wu; Ying Li; Shuxing Chen; Liuning Wang; Bangjie Chen; Fenglin Zhang; Ziran Zhang; Congjun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Nutritional status and drug resistance in EGFR-mutant NSCLC: a retrospective cohort study on almonertinib efficacy - Chao Wu; Ying Li; Shuxing Chen; Liuning Wang; Bangjie Chen; Fenglin Zhang; Ziran Zhang; Congjun Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Physiological and molecular responses to different sizes of polystyrene micro/nanoplastics in the model unicellular eukaryote Paramecium tetraurelia - Ping Ni; Congjun Li; Yu Fu; Naomi A. Stover; Lifang Li (Journal of Hazardous Materials, 2025)

Corrigendum to “A G219A hemagglutinin substitution increases pathogenicity and viral replication of Eurasian avian-like H1N1 swine influenza viruses” [Vet. Microbiol. 306 (2025) 110565] - Cong He; Xiaokun Hu; Junmei Huang; Congjun Jia; Mengling Zhang; Weilin Xu; Meidi Li; Mengkai Cai (Veterinary Microbiology, 2025)

A G219A hemagglutinin substitution increases pathogenicity and viral replication of Eurasian avian-like H1N1 swine influenza viruses - Cong He; Xiaokun Hu; Junmei Huang; Congjun Jia; Mengling Zhang; Weilin Xu; Meidi Li; Mengkai Cai (Veterinary Microbiology, 2025)

Comparative transcriptome analysis reveals the response mechanism of the typical marine ciliate Euplotes vannus to heavy metal cadmium exposure - Yingxuan Tian; Congjun Li; Yu Fu; Eleni Gentekaki; Lifang Li (Marine Environmental Research, 2025)

Multiple biological responses and transcriptome plasticity of the model unicellular eukaryote paramecium for cadmium toxicity aggravated by freshwater acidification - Congjun Li; Haitao Wang; Yu Fu; Eleni Gentekaki; Yulin Guo; Lifang Li (Environmental Pollution, 2025)

Decabromodiphenyl ethane (DBDPE) inhibited the growth and feeding by disrupting the gut and digestive gland homeostasis in octopus Amphioctopus fangsiao (Mollusca: Cephalopoda) - Jian Zheng; Congjun Li; Shuwen Li; Xiaodong Zheng (Science of The Total Environment, 2024)

Source-to-sink processes and genetic mechanism of progradational and lateral accretion submarine fans in the Qiongdongnan Basin, South China Sea - Congjun Feng; Guozhang Fan; Zhili Yang; Xingzong Yao; Xinglei Song; Weiqiang Li; Hongjun Qu; Qiang Zhang; Xuefeng Wang (Frontiers in Marine Science, 2024)
Submarine fan reservoirs are important accumulation zones for oil, gas, and natural gas hydrates, offering significant potential for hydrocarbon exploration. During the deposition period of the Sanya Formation in the southern part of the Changchang Sag of the Qiongdongnan Basin, a large submarine fan developed. However, the internal structure, source-sink system, and formation mechanism of this fan remain poorly understood, posing significant challenges to exploration in this area. This paper examines the source-to-sink sedimentary processes and deposition of submarine fans, using the Changchang Sag, in the Qiongdongnan Basin in the Northern South China Sea, as an example, which will provide valuable general guidance for deep water oil and gas exploration. Based on the theories of seismic stratigraphy and seismic sedimentology, this paper utilizes techniques such as seismic facies analysis, seismic attribute optimization, paleogeomorphology reconstruction, and source-to-sink sedimentary system analysis to analyze the 3D seismic data of the study area. Research indicates that the Sanya Formation in the Changchang Sag of the Qiongdongnan Basin comprises three depositional units: submarine fan, feeder channel, and Semi-deep marine to deep marine mudstone. The submarine fan is a fan formed by the coupling and convergence of submarine fans sourced from the southwest and southeast. Internally, it is divided into three sub-facies: the proximal fan of the sand-rich submarine fan, the main body of the sand-rich submarine fan lobes, and the distal lobes of the sand-rich submarine fan. The submarine fan sourced from the southwest extends nearly north-south and is primarily fed by sediment transported through three large, banded ancient valleys. The sedimentary filling is characterized by three-phase progradation. The submarine fan sourced from the southeast extends nearly east-west and is primarily fed by sediment transported through a single large, banded ancient valley. The sedimentary filling is characterized by two-phase lateral accumulation. During the deposition period of the Sanya Formation, certain areas of the southern uplift belt were exposed for extended periods and subjected to weathering and erosion. Sediments are transported to large ancient valleys through small supply channels. A large number of sediments were transported to the southern slope of the Changchang sag through the provenance channel system such as large ancient valleys and slope belts and deposited in the center of the sag. These make up a complete system of large ancient uplifts and submarine fan source-to-sink sedimentary systems.The sedimentary model is a lobed submarine fan controlled by semi-restricted ancient valleys and expansive basins.

The Middle Miocene lobe-shaped and band-shaped submarine fans in the Lingshui Sag, Qiongdongnan Basin: source-to-sink system, genesis and implication - Xingzong Yao; Congjun Feng; Hongjun Qu; Min Zhang; Daming Li (Acta Oceanologica Sinica, 2024)

Fabrication and characterization of polyvinyl alcohol/sodium alginate loaded carvacrol/silica hollow microspheres composite hydrogel as a colourimetric freshness indicator - Hongdan Hao; Bingchao Duan; Lidan Zhang; Lan Wang; Lingli Zhang; Yufei Wang; Yuanyuan Li; Chunmei Zhao; Guochao Jia; Yuling Li; Congjun Liu; Kui Lu (Food Bioscience, 2024)

Red and blue light promote tomato fruit coloration through modulation of hormone homeostasis and pigment accumulation - Yanna Xu; Congjun You; Changbin Xu; Chaofan Zhang; Xiaoli Hu; Xiaolong Li; Haijie Ma; Jinli Gong; Xuepeng Sun (Postharvest Biology and Technology, 2024)

Impacts of species depletion on the food web structure of a marine ecosystem based on topological network analysis - Congjun Xu; Jun Xu; Fan Li; Yiping Ren; Ying Xue (Acta Oceanologica Sinica, 2023)

Deciphering the degradation characteristics of the fungicides imazalil and penflufen and their effects on soil bacterial community composition, assembly, and functional profiles - Lingxi Han; Han Xu; Qianwen Wang; Xiaoli Liu; Xiaoming Li; Yiran Wang; Jiyun Nie; Mingyu Liu; Chao Ju; Congjun Yang (Journal of Hazardous Materials, 2023)

Societal benefits and environmental performance of Chinese aquaculture - Congjun Xu; Guohuan Su; Kangshun Zhao; Xianghong Kong; Hongxia Wang; Xiaoqi Xu; Ziqi Li; Min Zhang; Jun Xu (Journal of Cleaner Production, 2023)

Assessing sustainable performance of aquatic species using multiple footprints for comprehensive dietary advice - Congjun Xu; Guohuan Su; Kangshun Zhao; Xiaoqi Xu; Ziqi Li; Min Zhang; Jun Xu (Journal of Cleaner Production, 2023)

Comparative transcriptome and antioxidant biomarker response reveal molecular mechanisms to cope with zinc ion exposure in the unicellular eukaryote Paramecium - Congjun Li; Yu Fu; Yingxuan Tian; Zihan Zang; Eleni Gentekaki; Zhenyuan Wang; Alan Warren; Lifang Li (Journal of Hazardous Materials, 2023)

Dietary intake of microplastics impairs digestive performance, induces hepatic dysfunction, and shortens lifespan in the annual fish Nothobranchius guentheri - Kun Xiao; Lili Song; Yishuai Li; Congjun Li; Shicui Zhang (Biogerontology, 2023)

Assessment of greenhouse gases emissions and intensity from Chinese marine aquaculture in the past three decades - Congjun Xu; Guohuan Su; Kangshun Zhao; Huan Wang; Xiaoqi Xu; Ziqi Li; Qiang Hu; Jun Xu (Journal of Environmental Management, 2023)

Dietary intake of GDF11 delays the onset of several biomarkers of aging in male mice through anti-oxidant system via Smad2/3 pathway - Lili Song; Fei Wu; Congjun Li; Shicui Zhang (Biogerontology, 2022)

Dietary intake of diosgenin delays aging of male fish Nothobranchius guentheri through modulation of multiple pathways that play prominent roles in ROS production - Lili Song; Congjun Li; Fei Wu; Shicui Zhang (Biogerontology, 2022)

Identification of Isthmin1 in the small annual fish, Nothobranchius guentheri, as a novel biomarker of aging and its potential rejuvenation activity - Congjun Li; Lili Song; Yang Zhou; Jiangshui Yuan; Shicui Zhang (Biogerontology, 2022)

Research on 3D geological modeling method based on multiple constraints - Ming Hao; Minghui Li; Jianlong Zhang; Yujie Liu; Congjun Huang; Fang Zhou (Earth Science Informatics, 2021)

Genomic regions showing copy number variations associate with resistance or susceptibility to gastrointestinal nematodes in Angus cattle - Yali Hou; George E. Liu; Derek M. Bickhart; Lakshmi K. Matukumalli; Congjun Li; Jiuzhou Song; Louis C. Gasbarre; Curtis P. Van Tassell; Tad S. Sonstegard (Functional & Integrative Genomics, 2012)

Characterization of the rumen microbiota of pre‐ruminant calves using metagenomic tools - Robert W. Li; Erin E. Connor; Congjun Li; Ransom L. Baldwin, VI; Michael E. Sparks (Environmental Microbiology, 2012)
Summary The temporal sequence of microbial establishment in the rumen of the neonatal ruminant has important ecological and pathophysiological implications. In this study, we characterized the rumen microbiota of pre‐ruminant calves fed milk replacer using two approaches, pyrosequencing of hypervariable V3–V5 regions of the 16S rRNA gene and whole‐genome shotgun approach. Fifteen bacterial phyla were identified in the microbiota of pre‐ruminant calves. Bacteroidetes was the predominant phylum in the rumen microbiota of 42‐day‐old calves, representing 74.8% of the 16S sequences, followed by Firmicutes (12.0%), Proteobacteria (10.4%), Verrucomicrobia (1.2%) and Synergistetes (1.1%). However, the phylum‐level composition of 14‐day‐old calves was distinctly different. A total of 170 bacterial genera were identified while the core microbiome of pre‐ruminant calves included 45 genera. Rumen development seemingly had a significant impact on microbial diversity. The dazzling functional diversity of the rumen microbiota was reflected by identification of 8298 Pfam and 3670 COG protein families. The rumen microbiota of pre‐ruminant calves displayed a considerable compositional heterogeneity during early development. This is evidenced by a profound difference in rumen microbial composition between the two age groups. However, all functional classes between the two age groups had a remarkably similar assignment, suggesting that rumen microbial communities of pre‐ruminant calves maintained a stable function and metabolic potentials while their phylogenetic composition fluctuated greatly. The presence of all major types of rumen microorganisms suggests that the rumen of pre‐ruminant calves may not be rudimentary. Our results provide insight into rumen microbiota dynamics and will facilitate efforts in formulating optimal early‐weaning strategies.